Caracterización fenotípica y molecular de dos poblaciones de Panicum coloratum var. makarikariense - Moresco Lirusso, María Florencia (2021)
Panicum coloratum is a species of C4 type grass native to South Africa. In Argentina it is valued for its production of good quality forage in environments where resources are limiting, although it is scarcely diffused in current livestock systems. The purpose of this study was to evaluate the potential of two cultivars of Panicum coloratum var. makarikariense with respect to caryopses drop, germination and panicle morphology. Drop was evaluated weekly using caryopse traps. The results showed significant differences between cultivars in both years. The caryopses fall peak occurred on the same date for both cultivars, although that occurred in different weeks. The behavior was not influenced by environmental conditions and both cultivars produced seeds with high germination percentages in the different treatments. High variance and positive, high and significant correlations were found for various variables referring to panicle morphology, by means of the Principal Component Analysis for both years and for all the data as a whole. In all cases, the first two Principal Components were able to explain a high percentage of the total variability. Heritability estimates in the narrow sense were also made using the progeny-parent regression method for the trait "caryopsis drop" over two years. The estimates were made on the aforementioned morphological character, having previously selected 18.75% of the individuals of the Kapivera cultivar and 28.57% of the individuals of the Bambatsi cultivar. The only significant value obtained was in week 5, which gives an indication of the existence of additive genetic variance and also its stability. The results achieved with respect to h2 for the other weeks under study were statistically non-significant, indicating the absence of additive variance for the trait under study compared to the genetic context. The ISSR molecular markers allowed to confirm the existence of genetic variability between cultivars and within individuals of the same cultivar through bands and unique alleles per genotype. The individuals of the Kapivera cultivar have been able to genetically differentiate themselves from the individuals of the Bambatsi cultivar by detecting loci and alleles that differentiate both cultivars. These markers proved to be effective for the distinction of the cultivars analyzed and a wide variability has been observed in the species. The information provided in this work enriches the knowledge of the behavior of the main phenotypic characters associated with the performance of Panicum coloratum var. makarikariense, offering tools to assist genetic improvement in the search for an increase in crop yield. The characterization of the genetic diversity within the cultivars of P. coloratum var. makarikariense using ISSR markers widely used in grasses constitutes a fundamental step for its potential incorporation into breeding programs developed in the species.